Induction of ovulation. Issue 11 (November 2016) - Gebeh, Alpha; Metwally, Mostafa
Abstract: Anovulatory infertility is one of the commonest causes of infertility and can be caused by problems related to the ovary (normogonadotropic and hypergonadotropic hypogonadism) or the pituitary and hypothalamus (hypogonadotropic hypogonadism). Consequently induction of ovulation will depend on the cause of infertility. For those with normogonadotropic hypogonadism, ovulation can be induced using antioestrogens such as clomifene citrate and tamoxifen or aromatase inhibitors such as letrozole. Second line treatments include metformin, gonadotropins and laparoscopic ovarian drilling. Those with hypogonadotropic hypogonadism will require gonadotropins or GnRH analogues. The following review outlines the different approaches to ovulation induction with a focus on commonly encountered clinical scenarios.